Germany's trade with Latin America - Bernhard Klinner (Intereconomics, 1978)
This study analyses the development of the Federal Republic's foreign trade relations with 20 Latin American states within the 15 years from 1963 to 1977. It examines primarily the exchange of goods between the Federal Republic and the seven most important Latin American countries which on an average of the last 15 years accounted for more than 75% of the German foreign trade with the Central and South American states.
Keywords: 330; Latin America